Revisiting Corporate Governance in Emerging Economies: The Role of Board Size and Independence in Indonesian Banks - Samsul Bahari; Suriadi; Wa Ode Alzarliani; La Ode Sumail (Yayasan Ilomata, 2026)
Corporate governance remains a critical determinant of organizational performance in emerging markets, particularly in the banking sector, where transparency and accountability are essential. This study examines how board composition specifically board size and board independence affects financial performance among 38 Indonesian foreign exchange banks from 2017 to 2021. Using panel data regression with fixed effects, validated through Chow and Hausman tests, the study controls for unobserved heterogeneity and firm-specific characteristics. Results show that board size has a statistically significant positive association with both Return on Assets (ROA) and Return on Equity (ROE). From the perspective of Resource Dependence Theory, this relationship may reflect broader access to expertise and external resources associated with larger boards rather than a directly observed improvement in internal decision-making processes. However, board independence does not significantly impact financial outcomes, suggesting that structural independence lacks effectiveness without supporting institutional and cultural frameworks. These findings highlight the need for governance reforms emphasizing functional independence, director training, and stronger enforcement mechanisms to improve oversight. The study contributes to the literature by contextualizing Resource Dependence Theory within Indonesia’s institutional environment and offering insights for tailoring international governance standards to local realities. Overall, the results underscore that governance effectiveness depends not merely on structure but on institutional capacity and cultural adaptation, providing guidance for policymakers and future research.